Direct Growth of a GaInP/GaAs/Si Triple‐Junction Solar Cell with 22.3% AM1.5g Efficiency. Issue 12 (5th September 2019) - Feifel, Markus; Lackner, David; Ohlmann, Jens; Benick, Jan; Hermle, Martin; Dimroth, Frank
Abstract : III–V on Si multijunction solar cells exceede the efficiency limit of Si single‐junction devices but are often challenged by expensive layer transfer techniques. Here, progress in the development of direct epitaxial growth for GaInP/GaAs/Si triple‐junction solar cells is reported. III–V absorbers with a total thickness of 4.9 μm are grown onto a Si bottom cell using metal organic vapor phase epitaxy. A new record efficiency of 22.3% under AM1.5g conditions is reached herein, outperforming the previous value of 19.7%. This improvement is possible through better nucleation conditions for the first GaP layer on Si and consequently the reduction of threading dislocations within the III–V absorbers from 1.4 × 10 8 to 2.2 × 10 7  cm −2 . Further efficiency improvements toward 30% require even lower threading dislocation densities in the order of 1 × 10 6  cm −2, better light trapping in the Si bottom cell, and a reduction of parasitic absorption within the GaAs y P1– y graded buffer. Abstract : Progress in the development of expitaxial two‐terminal GaInP/GaAs/Si triple‐junction solar cells is reported. By reducing the defect density in the metamorphic III–V layers to a value of 2.2 × 10 7  cm −2, the conversion efficiency is increased from 19.7% to 22.3% under AM1.5g conditions. A detailed characterization of the device is provided to identify the main loss mechanisms.